Graduación. (UNED, 2023)
En la mesa principal aparecen de izquierda a derecha Jorge Enrique Guier Esquivel, el Rector - Chester Zelaya Goodman, Carlos Luis Fallas Monge, Marco Vinicio Álvarez Amador, Enrique Góngora Trejos